The consequences of flower colour polymorphism on the reproductive success of a neotropical deceptive orchid - Arida, B. L.; Pinheiro, F.; Laccetti, L.; Camargo, M. G.G. [UNESP]; Freitas, A. V.L.; Scopece, G. (Wiley, 2025)
Deceptive plants often exhibit elevated levels of polymorphism. The basis of the association between flower polymorphism and deceptive strategies, however, remains unclear. Epidendrum fulgens, a Neotropical deceptive orchid pollinated by butterflies, has an unexplored intrapopulation flower colour polymorphism. Here, we investigate the consequences of this polymorphism on its reproductive success. We performed field and common garden experiments, aiming to detect pollinator-mediated selection strength and direction over time, and test whether the presence of multiple colour morphs increases species' reproductive success. In the field, we monitored plant reproductive success and floral morphology on two populations over two flowering seasons and performed selection gradient analyses. In the common garden, we assembled plots of cultivated plants with same and different flower colour individuals (i.e., mono- and polymorphic plots), exposed them to pollinators and monitored their reproductive success. In both sites we also monitored the local pollinator community. In the field, colour morphs performed equally, but we found coherences between morphological differentiation and the direction of selection, which was very dynamic. In the common garden, mono- and polymorphic plots also performed equally, with highly variable reproductive success over time. We also found a highly diverse pollinator community. Our results suggest that flower polymorphism in E. fulgens is maintained by a combination of factors, including varying pollinator-mediated selection, assortative mating due to differential pollinator preferences and different phenotype heritability. Natural selection varied across time and space, indicating a dynamic interplay between pollinators and flower morphs.
Keywords: Epidendrum; floral traits; fluctuating selection; food deception; phenotypic polymorphism; pollinator-mediated selection